Antioxidant Activity of Endophytic Bacteria isolated from (Pyrrosia piloselloides) (L) M.G. Price - Achmad Arifiyanto; Salman Farisi (مجلة بغداد للعلوم, 2023)
Endophytic bacteria produced analogous secondary metabolites of their hosts. Similarly, the ability to generate antioxidants is not an exception. Dragon scales (Pyrrosia piloselloides), an epiphytic plant of the Polypodiaceae family, are frequently overlooked. This research aims to isolate antioxidant-producing bacteria from dragon-scale fern leaves. The antioxidant activities were tested after the extraction procedure using ethanolic extract. Bacteria were characterized and selected as candidates for antioxidant production by screening for the production of total phenolic compounds. Antioxidant levels were determined utilizing the ABTS, FRAP, and DPPH techniques. The preliminary findings of the entire phenolic compound test revealed that isolates B2, B3, C, and F produced the most phenolic compounds. The highest antioxidant activity was created by bacterial isolates B3. Bacterial isolates D1 have similar characteristics to B3 and it has been identified as Bacillus subtilis isolates D1AS. The assessment technique and extract dosages have the greatest effect on antioxidant concentration. In comparison to other approaches, the DPPH method yields considerable results when screening prospective isolates to manufacture antioxidants. Testing the ability of the results of bacterial extracts on other therapeutic effects needs to be done to ensure that the antioxidant abilities obtained in this study continue to be developed.